Natural Product Triterpenoids and Their Semi-Synthetic Derivatives with Potential Anticancer Activity - Ren, Yulin; Kinghorn, A. Douglas (Planta Medica, 2019)
Triterpenoids are distributed widely in higher plants and are of interest because of their structural diversity and broad range of bioactivities. In particular, there is a very large literature on the propensity of a variety of triterpenoids to act as potential anticancer agents. In the present review, the anticancer potential is summarized for naturally occurring triterpenoids and their semi-synthetic derivatives, including examples of lupane-, oleanane-, ursane-, and cucurbitane-type pentacyclic triterpenoids, along with dammarane-type tetracyclic triterpenes including ginsenosides and their sapogenins and dichapetalins, which have been characterized as antitumor leads from higher plants. Preliminary structure-activity relationships and reported mechanisms of the antineoplastic-related activity are included. Prior studies for triterpenoids of plant origin are supportive of additional work being conducted on the more detailed biological and mechanistic evaluation for the progression of this type of natural products as possible cancer chemotherapeutic agents.
Keywords: natural products; triterpenoids; antitumor activity; synthetic derivatives; structure-activity relationships; mechanisms of anticancer activity